2009
DOI: 10.1128/mcb.00708-09
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Alternative DNA Recognition by Maf Transcription Factors

Abstract: Maf transcription factors constitute a family of the basic region-leucine zipper (bZip) factors and recognize unusually long DNA motifs (13 or 14 bp), termed the Maf recognition element (MARE). The MARE harbors extended GC sequences on each side of its core motif, which is similar to TRE or CRE (7 or 8 bp) recognized by the AP1 and CREB/ATF families, respectively. To ascertain the structural basis governing the acquirement of such unique DNA recognition, we determined the crystal structure of the MafG-DNA comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 43 publications
2
93
0
Order By: Relevance
“…A basic leucine zipper domain and an adjacent conserved CNC domain are the defining features of this family. The CNC proteins form heterodimers with small maf proteins (MafK/F/G), and those dimers bind to a specific DNA sequence, the antioxidant response element (ARE) (8). The CNC proteins have important roles in stress responses.…”
mentioning
confidence: 99%
“…A basic leucine zipper domain and an adjacent conserved CNC domain are the defining features of this family. The CNC proteins form heterodimers with small maf proteins (MafK/F/G), and those dimers bind to a specific DNA sequence, the antioxidant response element (ARE) (8). The CNC proteins have important roles in stress responses.…”
mentioning
confidence: 99%
“…Although most bZIP transcription factors are thought to bind relatively compact binding sites (SI Appendix, Fig. S21), Maf subfamily transcription factors recognize unusually long motifs (13-14 bp) via an unconventional conformation of the invariant arginine and asparagine residues within the basic region of all bZIP proteins (4). Similarly, a crystal structure of Pap1, a S. pombe bZIP transcription factor, complexed with DNA demonstrated that Pap1 target site specificity was also due to alternate positioning of these two residues (2).…”
Section: Discussionmentioning
confidence: 99%
“…In a manner analogous to the Maf proteins, we propose that the extended homology region could stabilize invariant bZIP residues in the conformation required for UPRE-2 recognition. With the exception of MafG, most bZIP crystal structures have been based on constructs truncated to include only 1-9 nucleotides N-terminal to the basic DNA binding region (4,(25)(26)(27)(28) (SI Appendix, Fig. S22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations